Proses Negosiasi Dalam Penetapan Ganti Rugi Pengadaan Tanah Guna Kepentingan Umum (Studi Kasus Pada Proyek TOL Ungaran-Bawen) - Sonia Fabe Berminas; Yuwanto .; Suwanto Adhi (Journal of Politic and Government Studies, 2014)
This research is aimed at getting the overview about the land procurement mecanism and the negotiation process for building of Ungaran – Bawen toll roads. This building of Ungaran – Bawen toll roads includes 9 (nine) village : Beji, Karangjati, Wringin Putih, Ngempon, Klepu, Derekan, Lemahireng, Kandangan, and Bawen. This construction project is planned will take 11,95 Km.From the result taken, shown that the problem that delayed the compensation issued for this project is the amount of the compensation itself. The process begun by the dealing for the location by the Central Java Governor by His decision No. 620/13/2005. later by the Major of Semarang Regency Decision No. 593.05/241 concerning The Officer Appointing for The Implementation of the Land-Obtaining for Public Interest of Semarang Regency. Mechanism of land in the construction of toll roads Ungaran – Bawen consisting of 4 (four) the process, namely planning, preparation, implementation ant the delivery of result. The steps up to the compensation payment are socializing, settling ROW, measuring, inventorying building and plant, publishing the measurement result, price discussing, compensating, land-right, releasing and certificating. Here the negotiations be vital processes in the implementation of the determination of the compensation. Even though negotiations has been done there are still people who do not agree with the amount of compensation being offered, until finally P2T take the final step is to conduct consignation, namely by depositing compensation to justice.Keywords : Negotiation, Compensation